SAXS and SANS Studies on the Phase‐Separated Network Structure of Amphiphilic Copolymer Composed of Poly(dimethyl siloxane) and Poly(N, N‐dimethyl acrylamide) Gels Swollen in Water and a Water/Methanol Mixture. Issue 1 (7th June 2019) - Yamamoto, Katsuhiro; Ito, Eri; Mori, Yuka
Abstract : The phase‐separated network structure of amphiphilic copolymer gels composed of poly(dimethyl siloxane) (PDMS) and poly( N, N ‐dimethyl acrylamide) (PDMAA) in water and a water/methanol mixture is investigated by small angle X‐ray (SAXS) and small angle neutron scatterings (SANS). The copolymerized gel of PDMS‐ co‐ PDMAA exhibits bicontinuous phase‐separated domains (hydrophilic and hydrophobic) with a periodicity at the nanometer scale, and the PDMS hydrophobic domain forms a cylinder‐like core. The hydrophilic region is confirmed to be selectively swollen by water and methanol. Deuterated water and deuterated methanol are used for the SAXS and SANS measurements. The electron density and scattering length density (SLD) of the hydrophilic region vary according to the mixture ratio and adsorption amount of the solvents. The SAXS profiles (curve and scattering intensity) significantly change with the ratio D2 O/methanol‐ d 4 . On the other hand, the SANS profiles do not change significantly. The deuterated solvents cannot be distributed into the PDMS domain (core). The solvents and PDMAA hydrophilic form matrix. In these situations, as for SANS, the SLD difference between the PDMS and matrix remains almost constant. As for SAXS, in contrast to SANS, the electron density difference between the PDMS and hydrophilic domain varies with the ratio of water to methanol. The SAXS and SANS profiles can be simulated using a core‐shell cylindrical model. We found that an interfacial thin region exists between the hydrophobic PDMS and hydrophilic PDMAA/solvents. This interfacial region is determined to be composed of a solvent–poor PDMAA.